2022
DOI: 10.3389/fendo.2022.976488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seawater and freshwater challenges on the Gh/Igf system in the saline-tolerant blackchin tilapia (Sarotherodon melanotheron)

Abstract: Prolactin (Prl) and growth hormone (Gh) as well as insulin-like growth factor 1 (Igf1) are involved in the physiological adaptation of fish to varying salinities. The Igfs have been also ascribed other physiological roles during development, growth, reproduction and immune regulation. However, the main emphasis in the investigation of osmoregulatory responses has been the endocrine, liver-derived Igf1 route and local regulation within the liver and osmoregulatory organs. Few studies have focused on the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Consistently, the present study revealed that prl mRNA transcripts increased from SW to 4 ppt and FW transfer on day 4 and day 8, and decreased significantly from FW to 0 ppt and SW transfer on day 4 and day 8 in the pituitary. The pituitary prl contributes to the fish systemic response to salinity changes [ 58 ]. prl regulates ion-conserving and water-secreting processes in osmoregulatory tissues such as the gills, kidney, intestine, and urinary bladder to mediate FW acclimation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the present study revealed that prl mRNA transcripts increased from SW to 4 ppt and FW transfer on day 4 and day 8, and decreased significantly from FW to 0 ppt and SW transfer on day 4 and day 8 in the pituitary. The pituitary prl contributes to the fish systemic response to salinity changes [ 58 ]. prl regulates ion-conserving and water-secreting processes in osmoregulatory tissues such as the gills, kidney, intestine, and urinary bladder to mediate FW acclimation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%